THE STATE AND PERSPECTIVES OF THE PENSION AND DISABILITY INSURANCE SYSTEM IN THE REPUBLIC OF SERBIA - ObradoviC, Goran (Ревија за социјална политика/Journal of Social Policy, 2015)
The paper deals with the current state of the system ofpension and disability insurance in the Republic of Serbia and the possibledirections of change. The author analyses the causes of an extremely poorstatus of the pension and disability insurance system, based on currentfinancing and intergenerational solidarity. The disadvantages of thissystem, in addition to its indisputable advantages, are also pronounced inother countries that apply it. However, in countries such as Serbia, thereare factors that further complicate its sustainability, such as poordemographic situation, high unemployment rate, and the like. In thiscontext, the text provides a brief overview of the measures taken to date,with the analysis of their short-term and long-term effects, Finally, theauthor gives a personal view of the direction of development of thepension and disability insurance system in the Republic of Serbia.